Outcomes and factors associated with survival of patients with HIV/AIDS initiating antiretroviral treatment in Liangshan Prefecture, southwest of China: A retrospective cohort study from 2005 to 2013. Issue 27 (July 2016) - Zhang, Guang; Gong, Yuhan; Wang, Qixing; Deng, Ling; Zhang, Shize; Liao, Qiang; Yu, Gang; Wang, Ke; Wang, Ju; Ye, Shaodong; Liu, Zhongfu
Abstract : Abstract: Human immunodeficiency virus (HIV)–positive cases have been reported among people who injected drugs in Liangshan Prefecture in southwest of China since 1995 and Liangshan has become one of the most seriously affected epidemic areas in China. In 2004, several patients with HIV/acquired immunodeficiency syndrome (AIDS) initiated antiretroviral treatment (ART) at the Central Hospital of Liangshan Prefecture. From 2005 to 2013, the number of patients receiving ART dramatically increased. We conducted a retrospective cohort study to analyze the long-term survival time and associated factors among patients with HIV/AIDS who received ART in Liangshan Prefecture for the first time. Data were collected from the Chinese AIDS Antiretroviral Therapy DATAFax Information System. A life table and the Kaplan–Meier and Cox proportion hazard regression were used to calculate the survival time and its associated factors, respectively. Among 8310 ART-naïve patients with HIV/AIDS who initiated ART, 436 patients died of AIDS-related diseases, and their median time of receiving ART was 15.0 ± 12.3 months, whereas 28.7% of them died within the first 6 months after treatment. The cumulative survival rates of those receiving ART in 1, 2, 3, 4, and 5 years were 97.1%, 93.4%, 90.6%, 88.8%, and 86.0%, respectively. Multivariate Cox regression analysis showed that male patients on ART were at a higher risk of death from AIDS-related diseases (adjusted hazard ratio [AHR] = 1.5, 95% confidence interval [CI]: 1.1–2.1) than female patients. Patients infected with HIV through injection drug use (IDU) were at a higher risk of death (AHR = 1.6, 95% CI: 1.2–2.2) than those infected through heterosexual transmission. Patients with a baseline CD4 cell count <50/mm 3 (AHR = 9.8, 95% CI: 6.0–15.9), 50–199/mm 3 (AHR = 3.3, 95% CI: 2.3–4.6), and 200–349/mm 3 (AHR = 1.7, 95% CI: 1.2–2.3) were at a higher risk of death than those with a CD4 cell count ≥350/mm 3 . ART prolonged survival time of patients with HIV/AIDS and improved their survival probability. Patients with HIV/AIDS should be consistently followed up and the CD4 T-cell count regularly monitored, and timely and early antiretroviral therapy initiated in order to achieve a better survival rate.